Neuroshyphilis as a lumbar polyradiculopathy: case report - Barra, Luiz Alberto Costa; Bedaque, Eleni A.; Martinelli, Fabio L.B.; Macedo, Débora C.; Oliveira, Augusto C.P. (Brazilian Journal of Sexually Transmitted Diseases, 2001)
Neurosyphilis occurs in 10 to 30% of untreated patients with syphilis, 5 to 35 years after the initial infection. Clinical manifestations are variable, affecting different topographies either in central or peripheral nervous system. In this report, a 48-year-old man presented with a 3- month history of progressive lumbar and legs pain, weakness and paresthesia, resulting in difficult walking. He sought for an orthopaedic center in Diadema-SP where hypothesis of prolapsed intervertebral disc was avoided by lumbar computerized tomography. CSF analysis concluded for neurosyphilis. The patient was referred to Instituto de Infectologia Emílio Ribas where therapy with crystalline penicillin was begun. He gradually recovered his muscular strength and his sensation over the following 21 days of treatment. To date, no symptoms or signs that could suggest recurrence have developed.